Human recombination hot spots hidden in regions of strong marker association. - Jeffreys, A; Neumann, R; Panayi, M; Myers, S; Donnelly, P (2005)
The fine-scale distribution of meiotic recombination events in the human genome can be inferred from patterns of haplotype diversity in human populations but directly studied only by high-resolution sperm typing. Both approaches indicate that crossovers are heavily clustered into narrow recombination hot spots. But our direct understanding of hot-spot properties and distributions is largely limited to sperm typing in the major histocompatibility complex (MHC). We now describe the analysis of an unremarkable 206-kb region on human chromosome 1, which identified localized regions of linkage disequilibrium breakdown that mark the locations of sperm crossover hot spots. The distribution, intensity and morphology of these hot spots are markedly similar to those in the MHC. But we also accidentally detected additional hot spots in regions of strong association. Coalescent analysis of genotype data detected most of the hot spots but showed significant differences between sperm crossover frequencies and historical recombination rates. This raises the possibility that some hot spots, particularly those in regions of strong association, may have evolved very recently and not left their full imprint on haplotype diversity. These results suggest that hot spots could be very abundant and possibly fluid features of the human genome.